Achievable Rate Region of Active RIS-Aided MISO Interference Channels - Long, Ruizhe; Chen, Hao; Liang, Ying-Chang (IEEE International Conference on Communications (2003), 2024)
This paper characterizes the achievable rate region of the active reconfigurable intelligent surface (RIS)-aided multiple-input single-output (MISO) interference channel, where an active RIS is used to help multiple multi-antenna transmitters send information to their intended receivers in the presence of strong interference among them. All the transmitters are subject to the transmit power constraints, while the active RIS must satisfy the power budget constraint and the maximum amplitude constraint for each reflecting element (RE). Under these constraints, the rate-profile method is employed to approach the Pareto boundary of the rate region, which needs to solve a series of feasibility problems for a given rate profile. These problems can be solved by an alternating optimization algorithm. In each iteration, the sum of the rate tuples is sequentially optimized by the transmit beamforming vectors at the transmitters and the reflection coefficients matrix at the active RIS. Specifically, the transmit beamforming vectors are obtained by solving a sequence of second-order cone programming (SOCP) problems, and the reflection coefficients matrix is obtained by solving a sequence of semidefinite programming (SDP) problems along with Gaussian randomization. Simulation results show that, even with strong interference, the active RIS can offer a significant improvement in the rate region compared to the passive RIS under the same power budget.